Does Self-Reported or Behavioral Impulsivity Predict Subjective Response to Low-Dose Alcohol?. (11th January 2019) - Berey, Benjamin L; Leeman, Robert F; Pittman, Brian; Franco, Nicholas; Krishnan-Sarin, Suchitra
Abstract : While non-treatment-seeking heavy drinkers reported increases in stimulation and sedation following low-dose alcohol, neither behavioral nor self-reported impulsivity was associated with alcohol responses. Future alcohol administration studies should consider mood states as they may be misconstrued as stimulant and/or sedative alcohol responses. Abstract: Aims: Subjective response to alcohol and impulsivity are both independent predictors of alcohol use and may be related risk factors for alcohol use disorders (AUDs). Recent findings suggest that more impulsive individuals may experience higher risk subjective response patterns at moderate-to-high doses of alcohol. However, whether these relationships are observable early in a drinking occasion remains an open question. This study examined multiple measures of impulsivity in relation to subjective response following low-dose alcohol. Method: Eighty-seven non-treatment-seeking heavy drinkers were enrolled in a placebo-controlled alcohol administration study testing the effects of NMDA receptor antagonist, Memantine. Baseline impulsivity assessments included the Cued Go/No-Go Task, Experiential Discounting Task, and Barratt Impulsiveness Scale, Version 11 (BIS-11). Following consumption of low-dose alcohol aimed to increase blood alcohol concentration (BAC) to 0.03%, subjective stimulation and sedation were measured using the Biphasic Alcohol Effects Scale. Models were tested to relate impulsivity measures to subjective response with a post hoc exploratory model exploring boredom as an alternate predictor. Results: Increases in stimulation and sedation were observed following low-dose alcohol, but were not predicted significantly by impulsivity measures. Although greater impulsivity on the BIS-11 was a trend-level predictor of increased sedation, post hoc analyses suggested these results were an artifact of boredom. Conclusion: Although impulsivity did not predict subjective response to low-dose alcohol, the results suggest that small amounts of alcohol can produce a range of subjective effects, even among heavy drinkers. Future studies would benefit by examining subjective response across a range of BACs among both light and heavy drinkers.